2020
DOI: 10.1002/pol.20200032
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation dynamics of blends ofPVDFand zwitterionic copolymer by dielectric relaxation spectroscopy

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…After 100 Hz, the dielectric constant is nearly constant and loss tangent shows minima due to α c or dipole relaxation process in this region corresponding to the crystalline region of the polymer (Figure 4a,b and Figure S8a,c). 57 The high‐frequency α a relaxation, also called glass transition relaxation corresponds to the amorphous phase of the material (Figure S8b,d) 58–62 . It is observed that after hot press loss tangent peak in the high‐frequency region diminishes, which can be explained by an increase in crystallinity or a decrease in the amorphous phase of the material (Figure 4b and Figure S6b).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…After 100 Hz, the dielectric constant is nearly constant and loss tangent shows minima due to α c or dipole relaxation process in this region corresponding to the crystalline region of the polymer (Figure 4a,b and Figure S8a,c). 57 The high‐frequency α a relaxation, also called glass transition relaxation corresponds to the amorphous phase of the material (Figure S8b,d) 58–62 . It is observed that after hot press loss tangent peak in the high‐frequency region diminishes, which can be explained by an increase in crystallinity or a decrease in the amorphous phase of the material (Figure 4b and Figure S6b).…”
Section: Resultsmentioning
confidence: 96%
“…57 The high-frequency α a relaxation, also called glass transition relaxation corresponds to the amorphous phase of the material (Figure S8b,d). [58][59][60][61][62] It is observed that after hot press loss tangent peak in the high-frequency region diminishes, which can be explained by an increase in crystallinity or a decrease in the amorphous phase of the material (Figure 4b and Figure S6b). The dielectric constant and loss tangent increase with an increase in temperature for PNC0, PNCZ1.00 and HPZ3L samples (Figure S8e,f).…”
Section: Dielectric Propertiesmentioning
confidence: 97%
“…Normally, the U e of the polymer film is obtained by the equation U e ¼ Ð EdD, where E is the applied electric field and D is the electrical displacement. 8 For linear dielectrics, the expression is simplified as U e = 1/2e 0 e r E 2 , where e 0 and e r represent the dielectric constant of the vacuum and medium. 9,10 Various strategies have been proposed to achieve high energy capacity of the polymer, among which the introduction of high-k inorganic nanofillers in the polymer composite is an acknowledged solution.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, the U e of the polymer film is obtained by the equation , where E is the applied electric field and D is the electrical displacement. 8 For linear dielectrics, the expression is simplified as U e = 1/2 ε 0 ε r E 2 , where ε 0 and ε r represent the dielectric constant of the vacuum and medium. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…Due to the formation of the dipole–dipole physical cross-links, many polyzwitterions have exceptionally high glass transition temperatures that cannot be measured using conventional calorimetry due to the onset of thermal degradation. ,, Fast scanning calorimetry (FSC) has recently emerged as a powerful tool to minimize thermal degradation and observe thermal properties that have been unobservable using the slower rates found in conventional DSC. , By heating and cooling at rates on the order of 1000 K/s, thermal degradation can often be avoided and the sample can be reversibly heated and cooled . FSC has been shown to be as effective at measuring the fragility of a material as conventional methods such as rheology, dielectric relaxation, and DSC, while also being able to scan over a larger range of cooling rates. ,,,, …”
Section: Introductionmentioning
confidence: 99%